Síntese de derivados de aminoácidos contendo selênio ou telúrio miméticos da enzima glutationa peroxidase - Alberto, Eduardo Eliezer (2007)
This work presents the synthesis of aminoacid derivatives containing selenium or tellurium. The synthetic strategy employed herein afforded the target compounds in a two-step route. Besides, it awarded a modular characteristic to the products, allowing a quick synthesis of a small library of new compounds with high structural diversity. The synthetic approach employed the amide bond formation between bromocarboxylic acids 1a-c and L-valine and L-phenylalanine methyl ester 2a and 2b respectively. The bromoacetic acid 1a, 3-bromopropionic acid 1b and 4- bromobutyric acid 1c were treated with base and ethyl chloroformate to produce the mixed anhydride in situ, which was then reacted with the aminoesters to form the key intermediates 3a-e in high yields. [...]